2006
DOI: 10.1002/yea.1394
|View full text |Cite
|
Sign up to set email alerts
|

Key physiological differences in Candida albicans CDR1 induction by steroid hormones and antifungal drugs

Abstract: The Candida albicans CDR1 gene, encoding an ABC transporter that functions as an efflux pump, is thought to be involved in pathogenic adaptation and uses mammalian hormones and other environmental cues to regulate its activity. Exposure of several clinical isolates of C. albicans to 1 × 10 −8 M 17β-oestradiol increased CDR1 expression and the isolates showed a positive correlation between oestrogen induction of CDR1 and growth in the presence of oestrogen. A reporter strain carrying the GFP gene under the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…6a). Using the C. albicans CaSA1 strain, which expresses GFP under the control of the CDR1 promoter24, we further observed that mutation of mir-251 or mir-252 reduced the relative fluorescence intensity of CaSA1::GFP in both the proximal and distal intestine in nematodes (Fig. 6b).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…6a). Using the C. albicans CaSA1 strain, which expresses GFP under the control of the CDR1 promoter24, we further observed that mutation of mir-251 or mir-252 reduced the relative fluorescence intensity of CaSA1::GFP in both the proximal and distal intestine in nematodes (Fig. 6b).…”
Section: Resultsmentioning
confidence: 73%
“…C. albicans infection can reduce lifespan, and increase the expression of some antimicrobial genes13. In this study, we used the CaSA1 strain, which carries the GFP gene under the control of CDR1 promoter24, to further examine the persistence of C. albicans cells within the pharynx and the intestine of C. elegans . In contrast to E. coli OP50 and heat-killed C. albicans CaSA1, live C. albicans CaSA1 cells accumulated dramatically in the pharyngeal grinder organ, and in the proximal, middle, and distal intestine of C. elegans (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Expression is increased by gain-of-function mutations in CaTac1p, with highlevel drug resistance occurring when this mutation is brought to homozygosity by loss of heterozygosity (55,324). High doses of the female steroid hormone progesterone transiently upregulate, via steroid-specific PDREs, the same core of closely related ABC transporters induced by antifungal intervention or gain-of-function mutations in the transcription factors (21,185). In some instances, FLC-resistant clinical isolates overexpress the MFS transporter CaMdr1p (232).…”
Section: Pathogenic Fungimentioning
confidence: 99%
“…Strains and Media C. albicans isolates YEM30, SC5314, CA2, 11) CA10 11) and CASA1 with green fluorescent protein (GFP) tagged CDR1 12) were used in this study and stored in culture medium supplemented with 10% (v/v) glycerol at −80°C. The isolates were propagated in YPD medium plates containing 2% agar at 30°C, inoculated into liquid YPD medium (2% tryptone, 1% yeast extract, 2% glucose) and incubated overnight in an orbital shaker (100 rpm) at 30°C.…”
Section: Methodsmentioning
confidence: 99%